2011
DOI: 10.1002/ajpa.21616
|View full text |Cite
|
Sign up to set email alerts
|

Paternal lineages signal distinct genetic contributions from British Loyalists and continental Africans among different Bahamian islands

Abstract: Over the past 500 years, the Bahamas has been influenced by a wide array of settlers, some of whom have left marked genetic imprints throughout the archipelago. To assess the extent of each group's genetic contributions, high-resolution Y-chromosome analyses were performed, for the first time, to delineate the patriarchal ancestry of six islands in the Northwest (Abaco and Grand Bahama) and Central (Eleuthera, Exuma, Long Island, and New Providence) Bahamas and their genetic relationships with previously publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 66 publications
3
13
0
Order By: Relevance
“…In addition, genome-wide data have suggested that patterns of genetic ancestry in Cuba, Puerto Rico and Hispaniola (the Greater Antilles) were consistent with a model of two migration events from different regions of western Africa, implying that Afro-Caribbean populations have mixed African ancestry [102•]. These results are also congruent with a Y-chromosome study that found diverse haplotypes in Afro-Caribbeans from the Bahamas that were inferred to originate from different ethnic groups within West Central Africa [103]. Furthermore, isotope data from skeletal remains of enslaved Africans in Barbados suggested that first generation captives had different dietary histories likely due to differences in their geographic origins in Africa [104].…”
Section: Signatures Of the Trans-atlantic Movementsupporting
confidence: 64%
“…In addition, genome-wide data have suggested that patterns of genetic ancestry in Cuba, Puerto Rico and Hispaniola (the Greater Antilles) were consistent with a model of two migration events from different regions of western Africa, implying that Afro-Caribbean populations have mixed African ancestry [102•]. These results are also congruent with a Y-chromosome study that found diverse haplotypes in Afro-Caribbeans from the Bahamas that were inferred to originate from different ethnic groups within West Central Africa [103]. Furthermore, isotope data from skeletal remains of enslaved Africans in Barbados suggested that first generation captives had different dietary histories likely due to differences in their geographic origins in Africa [104].…”
Section: Signatures Of the Trans-atlantic Movementsupporting
confidence: 64%
“…These studies indicate that among African Caribbean populations found in Jamaica, Haiti, the Bahamas, St. Thomas, Barbados, and Trinidad and Tobago, there is about 65-95% African ancestry, 4-27% European ancestry, and 0-6% Native American ancestry (Parra et al, 1998;Molokhia et al, 2003;Miljkovic-Gacic et al, 2005;Benn-Torres et al, 2008;Simms et al, 2008Simms et al, , 2010Simms et al, , 2011Murray, 2010;Wilson et al, 2012). Generally, triparental admixture estimates are quite similar between these Anglophone islands.…”
Section: Discussionmentioning
confidence: 93%
“…Nonetheless, the admixture estimates observed in the sampled populations are comparable with the estimates of previous research that used autosomal markers. These studies indicate that among African Caribbean populations found in Jamaica, Haiti, the Bahamas, St. Thomas, Barbados, and Trinidad and Tobago, there is about 65-95% African ancestry, 4-27% European ancestry, and 0-6% Native American ancestry (Parra et al, 1998;Molokhia et al, 2003;Miljkovic-Gacic et al, 2005;Benn-Torres et al, 2008;Simms et al, 2008Simms et al, , 2010Simms et al, , 2011Murray, 2010;Wilson et al, 2012). Ancestry studies based on uniparentally inherited markers also show that for African Caribbean people in general, African woman, African men and European men made the most substantial genetic contributions to contemporary populations (Benn Torres et al, 2007;Deason et al, 2011Deason et al, , 2012Gaieski et al, 2011;Simms et al, 2012a,b;Benn Torres et al, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…It is worth noting that three additional A1b chromosomes have been recently found in Caribbean populations, which exhibit substantial Y-STR haplotype sharing with Y chromosomes from Gabon [35], [36]. Taken together, all these data reinforce the hypothesis of an origin in the north-western quadrant of the African continent for the A1b haplogroup [16], and, together with recent findings of ancient Y-lineages in central-western Africa [19], provide new evidence regarding the geographical origin of human MSY diversity.…”
Section: Discussionmentioning
confidence: 99%